Risk, capital buffer and bank lending: a granular approach to the adjustment of euro area banks - Laurent Maurin; Mervi Toivanen (European Central Bank (ECB), 2012)
We develop a partial adjustment model in order to estimate the factors contributing to banks' internal target capital ratio, lending policy and holding of securities. The model is estimated on a panel of listed euro area banks and country specific macrovariables. Firstly, banks' internal target capital ratios are estimated by using information on banks' riskiness and earnings capacity. Secondly, the impact of banks' capital gap on the credit supply and the security portfolio is estimated while controlling for the macroeconomic environment. An increase in bank' balance sheet risk is shown to increase the target capital ratios. The adjustment towards higher equilibrium capital ratios has a significant impact on banks' assets. The impact is found to be more sizeable on security holdings than on loans, thereby suggesting a pecking order.
Keywords: G01; G21; 330; banks; capital ratios; credit supply; euro area; partial adjustment model